Neisseria gonorrhoeae cervical spine epidural abscess requiring spinal decompression and instrumented fusion. Issue 5 (May 2023) - Fox-Lewis, Andrew; Luan, Kai; Hopkins, Christopher
Abstract: Disseminated gonococcal infection (DGI) is an uncommon complication of Neisseria gonorrhoeae infection, and typically presents with either a triad of tenosynovitis, dermatitis and polyarthralgia, or with extra-axial large joint septic arthritis. Spinal epidural abscess is a rare manifestation of DGI, with only a few previously reported cases, none of which required placement of metalware into the infected space. Here we report a severe case of isolated N. gonorrhoeae cervical spine epidural abscess necessitating surgical source control (C7/T1 laminectomy and debridement) and metalware placement (C6-T2 posterior instrumented fusion). The case was successfully managed by a combination of surgical intervention followed by six weeks of predominantly oral, targeted antimicrobial therapy.